Angina Outcomes in Secondhand Smokers: Results from the National Health and Nutrition Examination Survey 2007–2018 - Chaar, Suzanne; Yoon, Jeik; Abdulkarim, Joud; Villalobos, José; Garcia, Jeanette; López Castillo, Humberto (Avicenna Journal of Medicine, 2022)
Objective The aim of the study is to examine the relationship between secondhand smoke (SHS) and angina using the National Health and Nutrition Examination Survey database over a 12-year period.Methods Self-reported smoking status and cotinine levels were used to identify exposure groups (smokers, nonsmokers, and secondhand smokers), and medical history of angina was also collected via a self-report survey. The association between exposure to SHS and angina was analyzed using odd ratios with 95% confidence intervals calculated using two logistic regression models.Results The study found that when aggregating data from all 12 years, secondhand smokers are 42.9% significantly more likely to report having experienced angina, while smokers were 97.7% significantly more likely to report having angina compared with nonsmokers.Conclusions This study is the first of its kind to examine data from a national database over a 12-year period to determine an association between SHS and angina outcomes, thus highlighting the importance of reducing SHS exposure to improve cardiovascular health.
Keywords: secondhand smoke; cardiovascular health; environmental tobacco smoke; public policy; angina pectoris; coronary heart disease